2014
DOI: 10.1128/jvi.01926-14
|View full text |Cite
|
Sign up to set email alerts
|

Prime-Boost Immunization Strategies against Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) is a reemerging mosquito-borne alphavirus that causes debilitating arthralgia in humans. Here we describe the development and testing of novel DNA replicon and protein CHIKV vaccine candidates and evaluate their abilities to induce antigen-specific immune responses against CHIKV. We also describe homologous and heterologous prime-boost immunization strategies using novel and previously developed CHIKV vaccine candidates. Immunogenicity and efficacy were studied in a mouse model of CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 69 publications
3
58
0
2
Order By: Relevance
“…which a large portion (180 nucleotides) of the nsP3 replicase gene region has been deleted (9,10). We have shown that this deletion is stable and does not revert (9), and results in this study have extended and corroborated these findings.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…which a large portion (180 nucleotides) of the nsP3 replicase gene region has been deleted (9,10). We have shown that this deletion is stable and does not revert (9), and results in this study have extended and corroborated these findings.…”
Section: Resultssupporting
confidence: 79%
“…Accordingly, we infected a separate group of 6 naive cynomolgus macaques ( Figure 1; Δ5nsP3-B) with a dose of the Δ5 virus corresponding to that used for vaccination (1 × 10 5 plaque-forming units, PFU). The s.c. route of injection in the upper back (s.c., n = 4) was chosen to mimic the route used for vaccination and challenge, while the route of inoculation s.c. at the back of the wrist (i.w., n = 2) was used to allow monitoring of possible localized joint swelling as it was done in mouse models (8)(9)(10). Within the first days after infection, viremia could readily be detected in all animals ( Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations